2017
DOI: 10.1126/sciadv.1602024
|View full text |Cite
|
Sign up to set email alerts
|

Combining contact tracing with targeted indoor residual spraying significantly reduces dengue transmission

Abstract: Pairing location-based contact tracing and targeted indoor insecticide applications can effectively prevent dengue transmission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
110
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 109 publications
(116 citation statements)
references
References 52 publications
4
110
2
Order By: Relevance
“…Recent studies in other areas of Malaysia have also shown that dengue infection can occur at equivalent rates in both rural and urban areas (37, 38). It could be that the threshold human density required to maintain transmission may be lower than previously thought, although human movement (which may relate to population density) between urban and rural areas is also likely to have influenced the patterns we observed (39, 40).…”
Section: Discussionmentioning
confidence: 61%
“…Recent studies in other areas of Malaysia have also shown that dengue infection can occur at equivalent rates in both rural and urban areas (37, 38). It could be that the threshold human density required to maintain transmission may be lower than previously thought, although human movement (which may relate to population density) between urban and rural areas is also likely to have influenced the patterns we observed (39, 40).…”
Section: Discussionmentioning
confidence: 61%
“…Disease transmission is a major human health consequence of mosquito activity and, in many cases, management of mosquito- Pyrethroid insecticides are valuable tools for mosquito control because of their rapid action, high efficacy, low mammalian toxicity relative to some other insecticide groups and low cost 10 . Pyrethroids can be applied in a variety of ways such as thermal fogging of neighbourhoods 11 , internal domestic space and residual spraying 12,13 , as spatial repellents 14 , in lethal ovitraps 15 , as treatment of bed nets 16 and for impregnation of clothing 17 . These diverse applications have led to a dependency on pyrethroids around the world, but have also resulted in their overuse 18 .…”
Section: Althoughmentioning
confidence: 99%
“…aegypti as resting places, such as under beds and tables, inside closets and dark objects such as plastic crates and suitcases. This method uses less pesticide and has been successfully used to protect residences from dengue transmission (Vazquez-Prokopec et al, 2017).…”
Section: Adultmentioning
confidence: 99%